NARCISSISM IN LOCAL BUDGETING: THE MIRROR AND MASK EFFECTSOF PUBLIC ASPIRATION FUND - Pasoloran, Oktavian; Sukoharsono, Eko Ganis; Said, Darwis; Rura, Yohanis (Accounting Department,, 2015)
This study aims to interpret public aspiration fundin local budgeting in narcissism perspective. Discourse about